Assessing Service Quality Using SERVQUAL Model: An Empirical Study on Some Private Universities in Bangladesh - Hoque, Umma Salma; Akhter, Nazmoon; Absar, Nurul; Khandaker, Mayeen Uddin *; Al-Mamun, Abdullah (MDPI, 2023)
The increased competitive academic environment pushes higher institutions to improve their service quality for meeting the market demands. It is thus necessary to assess the factors that satisfy students and make them loyal to the university. This study has focused on assessing service quality, using the SERVQUAL Model to measure students’ satisfaction with private universities in Bangladesh. In the study, the primary data collection method through a questionnaire with the 5-point Likert scale was adopted to collect data from 229 students who are currently studying in different private universities in Chattogram, Bangladesh. Structural equation modeling (SEM) has been performed to analyze the data through the AMOS 22 statistical package. The findings report that a comfortable lecture room under the tangible dimension, providing service on time under the reliability dimension, the capacity of administrative staff to solve immediate problems under the responsiveness dimension, proficient lecturers for teaching and research under the assurance dimension, and focus of university management on students under the empathy dimension have a great influence on student satisfaction. The study concludes that managers and authorities of private universities must focus on ensuring better service quality as student satisfaction largely affects the sustainability and recurrence development of the institutions.